Trends in smoking prevalence in urban and rural China, 2007 to 2018: Findings from 5 consecutive nationally representative cross-sectional surveys. - Mei Zhang; Ling Yang; Limin Wang; Yong Jiang; Zhengjing Huang; Zhenping Zhao; Xiao Zhang; Yichong Li; Shiwei Liu; Chun Li; Linhong Wang; Jing Wu; et al. (PLoS Medicine, 2022)
Background Tobacco smoking is a leading cause of premature death in China, especially among adult men. Since the implementation of the Framework Convention on Tobacco Control in 2005, nationwide tobacco control has been strengthened, but its long-term impact on smoking prevalence is unclear. Methods and findings Five nationally representative surveys of the China Chronic Disease and Risk Factor Surveillance (CCDRFS) were conducted in 2007, 2010, 2013, 2015, and 2018. A total of 624,568 adults (278,605 men and 345,963 women) aged 18 to 69 years were randomly selected from 31 provinces (or equivalent) in China. Temporal changes in smoking prevalence and patterns (e.g., percentages of those smoking manufactured cigarettes, amount smoked, and age at smoking initiation) were analyzed, overall and by sex, urban or rural residence, year of birth, education and occupation, using linear regression methods. Among men, the standardized prevalence of current smoking decreased from 58.4% (95% confidence interval [CI]: 56.1 to 60.7) to 50.8% (95% CI: 49.1 to 52.5, p < 0.001) between 2007 and 2018, with annual decrease more pronounced in urban (55.7% [95% CI: 51.2 to 60.3] to 46.3% [95% CI: 43.7 to 49.0], p < 0.001) than rural men (59.9% [95% CI: 57.5 to 62.4] to 54.6% [95% CI: 52.6 to 56.6], p = 0.05) and in those born before than after 1980. Among rural men born after 1990, however, the prevalence increased from 40.2% [95% CI: 34.0 to 46.4] to 52.1% ([95% CI: 45.7 to 58.5], p = 0.007), with the increase taking place mainly before 2015. Among women, smoking prevalence remained extremely low at around 2% during 2007 to 2018. No significant changes of current smoking prevalence (53.9% to 50.8%, p = 0.22) were observed in male patients with at least 1 of major chronic diseases (e.g., hypertension, diabetes, myocardial infarction, stroke, chronic obstructive pulmonary disease (COPD)). In 2018, 25.6% of adults aged ≥18 years smoked, translating into an estimated 282 million smokers (271 million men and 11 million women) in China. Across 31 provinces, smoking prevalence varied greatly. The 3 provinces (Yunnan, Guizhou, and Hunan) with highest per capita tobacco production had highest smoking prevalence in men (68.0%, 63.4%, and 61.5%, respectively), while lowest prevalence was observed in Shanghai (34.8%). Since the children and teenage groups were not included in the surveys, we could not assess the smoking trends among youths. Furthermore, since the smoking behavior was self-reported, the smoking prevalence could be underestimated due to reporting bias. Conclusions In this study, we observed that the smoking prevalence has decreased steadily in recent decades in China, but there were diverging trends between urban and rural areas, especially among men born after 1980. Future tobacco control strategies should target rural young men, regions with high tobacco production, and patients suffering from chronic diseases.